Thanatophoric Dysplasia - Tria Sari Retno Asih; Roza Sriyanti (Andalas Obstetrics And Gynecology Journal, 2019)
Objective: Report a case of thanatophoric dysplasiaMethod: Case report Result: Case of a 25-year-old woman, with a diagnosis of gravid preterm G4P2A1H2 31-32 weeks + polyhydramnios + fetal hydrops, a single intrauterine live fetus with thanatophoric dysplasia. On ultrasound examination found fetal biometry; BPD: 7.78 cm, FL: 3.58 cm, HL: 3.11 cm, AC: 30.90 cm, HC: 28.48 cm AFI: 33.27 cm, a frontal bossing (+) picture appears, claver leaf skull (+) and micromelia (proximal, distal, phalanges). The ultrasound examination suggested Severe skeletal dysplasia (thanatophoric dysplasia), polyhydramnios, + single intrauterine live fetus + SC 1x scars. Then an amnioinfusion is performed and results are obtained. Chromosome analysis is carried out using the G-banding technique. Chromosomes have been studied from 20 cells from 3 different cell culture preparations and obtained the number of chromosomes in each cell studied is 46, XY which means the number of chromosomes 46 pieces with fetal sex chromosome XY. Mosaic chromosome abnormalities generally occur due to non-disjuntion in the mitotic phase after conception. At 33-34 weeks gestation, an infant was born by SC with birth weight: 1900 g, baby’s length: 31 cm, A / S 2/3.Conclusion : Thanatophoric dysplasia is a "lethal" skeletal dysplasia. A careful prenatal examination is needed in the diagnosis and termination of pregnancy.Keywords: Thanatophoric dysplasia, prenatal diagnosis